Long-term results of surgical treatment of a locally advanced rectal cancer using extrafascial principle of dissection - P. V. Tsarkov; I. A. Tulina; D. N. Fedorov; A. Yu. Kravchenko; O. Yu. Samofalova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate efficacy of extrafascial surgical interventions in patients with locally advanced cancer of rectum.Material and methods. From a prospective database of the patients treated in department of coloproctology and surgery of pelvic floor of B.V.Petrovsky Russian scientific center of surgery of Russian Academy of Medical Science from June, 2006 to December, 2009, serially admitted patients, who underwent surgical resection for cancer of rectum T1-4N0-2M0 were chosen for investigation. The first group included patients, with standard volume of operation (nervepreserving mesorectumectomy), the second group included patients with extended resections for locally advanced tumors adherent to neighbouring structures and organs, that was revealed in preoperative and/or intraoperative periods.Results. Original investigation evaluated results of treatment of 159 patients (87 men, mean age – 62 years), of them combined rectal surgery have been executed in 68 cases (43%). Locally advanced tumors were localized in low- and mid-ampullary regions of the rectum most often. The true tumor progression to resected structures and organs was revealed in 22% of the cases. Both in males and females resection of organs of genitourinary system, as well as the structures of a lateral pelvic wall was carried out most often. The overall mortality in studied cohort of patients was 1,9%. The two-year-old overall survival rate was nonsignificantly higher in patients after standard surgery (93,9%), than in the patients after extrafascial interventions (85,9%, р=0,18). The two-year cumulative relapse-free survival rate in group of standard operations (97,6%) appeared significantly higher, than in group of extrafascial resections: 92,4 and 88,2% respectively (р=0,02). Two-year cumulative cancer-specific survival rate did not differ significantly between groups of comparison - after standard resections this rate was 96,0%, after extrafascial surgery – 93,4% (р=0,37).Conclusions. Extrafascial resections for locally advanced rectal cancer doesn’t lead to decrease of overall and cancer-specific and cancer-specific survival rates in comparison to standard operations.